Social Judgment and Its Effect on EFL Students’ Confidence to Speak English in the Classroom - Anjeli Aulia Putri Arinda; Widya Caterine Perdhani (Universitas Pahlawan Tuanku Tambusai, 2026)
Confidence in speaking is a fundamental aspect of learning English as a foreign language (EFL); however, learners often experience anxiety triggered by the verbal feedback they receive during speaking activities. Although previous literature often highlights language anxiety in general, studies focusing specifically on how direct feedback affects students' confidence remain limited. This study investigates the effect of verbal feedback on the speaking confidence of students in the English Education Study Program at Brawijaya University. Using a descriptive qualitative design, data were collected through semi-structured interviews and analyzed thematically. The findings reveal that corrective feedback delivered directly and publicly can act as a cognitive disruptor, reducing focus and fluency while increasing fear of negative evaluation. Conversely, delayed, constructive, and supportive feedback can enhance students' confidence and willingness to communicate. This study concludes that the impact of verbal feedback is strongly determined by its timing, tone, and delivery, highlighting the importance of psychologically safe classroom interactions in developing EFL speaking skills.